Mechanical Properties of Bacterial Cement Mortar Integrating Natural Banana Fibres - Balachandran, Sunantha; Sudhakumar, Janardhanan; Thomas, Blessen Skariah; Sankaranarayanan, Pooja; Vasu, Suchithra Tharamel; Ravikumar, Arya Chithra (Applied Science and Engineering Progress, 2024)
This investigation analyzes the usage of bacterial content and different lengths of banana fiber reinforced with variable percentages in cement mortar. Portland pozzolana cement (PPC) was combined with bacterial solutions (Bacillus cereus) at a concentration of 1.15×104 cells/ml to produce a mortar composite. By adding natural fibers like banana fiber to the composite components, the mechanical behavior of the bacterial mortar was enhanced. Mortar mixtures using banana fibers with different fiber concentrations (0.25, 0.5, 0.75, and 1%) and lengths (0.5, 1, 1.5, and 2 cm) were evaluated. Compressive and flexural strength was found to be greatly affected by the addition of banana fibers to concrete, but only at lower fiber levels of up to 0.25% for all fiber lengths. At lower fiber levels of up to 0.25%, the length of the fiber had no discernible effect on compressive strength; however, at larger dosages exceeding 0.25%, shorter fibers were shown to outperform longer ones. However, the mixing of bacterial content in the mortar is not only significant to the mechanical properties but also potentially lowers the carbon emissions, making it a more sustainable option for composite preparation. The stability of bacterial-based mortar and its compatibility with natural fibers further underscores the potential for eco-friendly construction materials. By exploring the chemical and physical properties of banana fibers treated with alkali chemicals and their compatibility with bacterial cultures, this study adds depth to our understanding of these composite materials. Overall, the proposed methodology for preparing these composites holds promise for future applications in the construction industry, offering a sustainable and efficient alternative to traditional materials.